N′-(2-Fluorobenzylidene)acetohydrazide - Yang, Jie (International Union of Crystallography, 2010)
The title compound, C(9)H(9)FN(2)O, was prepared by the reaction between 2-fluorobenzophenone and acetohydrazide. In the crystal structure, inversion dimers linked by pairs of N—H⋯O hydrogen bonds occur, generating R (2) (2)(8) loops.